BASIC PROPERTIES IN RELATION TO DRYING PROPERTIES OF THREE WOOD SPECIES FROM INDONESIA - Efrida Basri; Nurwati Hadjib; Saefudin Saefudin (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2005)
The objectives of this study were to investigate basic and drying properties of three wood species from Indonesia, i.e. kuda (Lannea coromandelica Merr.), waru (Hibiscus tiliaceus L. and mindi besar (Melia dubia Cav.). The basic properties include density, shrinkages, modulus of rupture (MOR), compression parallel to grain (C//), wood strength and anatomical structures. Meanwhile, the drying properties included drying time and drying defects. The initial-final temperature and humidity for each species was based on defects that resulted from high temperature drying trial.The results showed that the drying properties were significantly affected by wood anatomical structure. The initial-final drybulb temperature and wetbulb depression for kuda wood are 50 -70ºC and 3-30ºC respectively, while the corresponding figures for waru wood are 65-80ºC and 6-30ºC, and for mindi besar wood are 55-80ºC and 4-30ºC. These drying schedules, however, still need further trial prior to their implementation in the factory-scale operation. All wood species studied have density and considerable strength recommended in their use for light medium construction purposes. Mindi besar wood has decorative appearance so it is suitable for furniture.